2021
DOI: 10.1177/0042098021989951
|View full text |Cite
|
Sign up to set email alerts
|

Do the characteristics of new green space contribute to gentrification?

Abstract: A number of recent studies have examined the socioeconomic functions and side effects of environmental amenity in urban development. In this study, an urban green space is viewed as both a positive and negative environmental externality because it could be a potential contributor to gentrification. Employing the difference-in-differences method at the public use microdata areas and census-tract level, this study examines the effects of new green space characteristics on multiple gentrification indicators in Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 58 publications
1
24
0
2
Order By: Relevance
“…On the other hand, a recent study of New York City parks showed a clear gentrification effect only in medium-sized parks, with no obvious effect in small and large parks [27]. The same study found that both passive-use and natural parks showed a greater gentrification effect compared to active-use (e.g., sports) green parks.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…On the other hand, a recent study of New York City parks showed a clear gentrification effect only in medium-sized parks, with no obvious effect in small and large parks [27]. The same study found that both passive-use and natural parks showed a greater gentrification effect compared to active-use (e.g., sports) green parks.…”
Section: Discussionmentioning
confidence: 89%
“…It is possible that gentrification effects might still occur over a longer period of time than the 17-year window analyzed herein. However, our span of observation is about the same range or longer as that used in previous studies showing green gentrification patterns, e.g., 9 years [27], 10 years [21], 11 years [37] and 5 years [38].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, Pearsall and Eller (2020) found that parks likely anchored gentrification in certain neighborhoods, but was not a driver of gentrification in others. Finally, Kim and Wu's (2021) study of parks in New York City revealed that park characteristics had an impact on gentrification outcomes over the medium-and long-term. While these three studies are all based on North American cities, our study contributes an additional line of evidence of the complexity of park-related gentrification based on a study in Latin America.…”
Section: Discussionmentioning
confidence: 99%
“…Gentrification is a process that occurs when historically disinvested neighborhoods experience economic revitalization that transforms their demographic, real estate and business characteristics [24], leading to an influx of new residents of higher SES and social privilege, and a transition towards a more educated, wealthier, whiter population, able to afford new or renovated, more expensive properties while also fomenting new cultural and consumption practices, finally changing the essential character of the neighborhood [22,[25][26][27]. The association between new neighborhood resources, such as the creation or restoration of greenspaces, and gentrification has been shown in a variety of cities worldwide [28], including Barcelona [29][30][31][32]. However, the direction of the causal pathway remains unclear [28,33].…”
Section: Are Greenspaces Associated With Neighborhood Gentrification Processes?mentioning
confidence: 99%